PRAKTIK-PRAKTIK CREATIVE ACCOUNTING - Fajri, Aminul (PERMANA, 2013)
There are many consequences in creative accounting. In an economic perspective, creative accounting is influenced by economic framework that aims for self-interset. This can only be done if it does not conflict with Generally Acceptable Accounting Principles (GAAP). Creative accounting is triggered by the pressure that the entities must be in profit to attract investors and resources. But this is more directed at deception or fraud in accounting practices. Is creative accounting is illegal or could be justified. Perceptions of creative accounting is still a thing that the pros and cons. Creative accounting is applied by the company because of some conditions, such as variations in accounting principles, in the context of the application of aggressive accounting principles (aggressive accounting), in the context of earnings management, financial reporting that really distorted (outright fraudulent financial reporting). Key words : Creative accounting, aggresive accounting, earnings management, outright fraudulent financial reporting.